The Competence Head of Junior High School National Standard Pondok Pesantren Based - Ubaidillah, Muhammad (Faculty of Education Universitas Negeri Malang, 2019)
The Junior High School National Standard has been programmed by the government continuously as an effort to adjust the demands of the times, and able to meet the quality requirements of graduates which in turn is an improvement on the quality of human resources. Including boarding school education based on non-formal, informal, and formal education with various advantages. The superiority of Junior High School National Standard based on the boarding school in boarding school Darus Sholah Jember lies in the system and educational value. This educational level is prepared to produce graduates who possess the noble knowledge, skills and noble character and spiritual emotions. .Keywords: Principal Competence, Pondok Pesantren